Asymptotic homogenization model for 3D grid-reinforced composite structures with generally orthotropic reinforcements - Kalamkarov, Alexander L.; Hassan, Essmat M.; Savi, Marcelo Amorim; Georgiades, Tasos (My University, 2009)
The asymptotic homogenization method is used to develop a comprehensive micromechanical model pertaining to three-dimensional composite structures with an embedded periodic grid of generally orthotropic reinforcements. The model developed transforms the original boundary-value problem into a simpler one characterized by some effective elastic coefficients. These effective coefficients are shown to depend only on the geometric and material parameters of the unit cell and are free from the periodicity complications that characterize their original material counterparts. As a consequence they can be used to study a wide variety of boundary-value problems associated with the composite of a given microstructure. The developed model is applied to different examples of orthotropic composite structures with cubic, conical and diagonal reinforcement orientations. It is shown in these examples that the model allows for complete flexibility in designing a grid-reinforced composite structure with desirable elastic coefficients to conform to any engineering application by changing some material and/or geometric parameter of interest. It is also shown in this work that in the limiting particular case of 2D grid-reinforced structure with isotropic reinforcements our results converge to the earlier published results.
Keywords: Asymptotic homogenization; Grid-reinforced composite structures; Orthotropic reinforcement; Effective elastic coefficients